Prospect of traditional dug wells for harvesting rainwater in Bastar region of Chhattisgarh: A case study - PRADHAN, ADIKANT; NAG, S. K.; CHANDRAKAR, T.; KERKETTA, A. (Journal of Soil and Water Conservation, 2021)
Open dug wells or chua (Kunwa) are more common traditional rainwater harvesting structures of Bastar region in Chhattisgarh, India. The yield of the wells has reduced over the years and 70% of them are now got dry or dwindled. Tokapal block had higher number of dug wells in the depth of 21 to 25m, otherwise remaining blocks had hardly reached the depth beyond 20 m except Jagdalpur and Bastanar with finger count open dug wells constructed above 25m. Drying time of open dug wells are unique features of the region. The most of the dug wells in rainfed areas were found drying in March and April. The pH ranges from 6.33 to 9.18, more than 8 pH were found in Karanpur, Alnar, Rampal, Upanpal, Bilauri and Jiragaon, only one wells had 9.18 pH and remainings were within 7 to 8. It was hardly found below 7.0 pH in Dondawal (6.33) and Bhaisabandha (6.83). Among the samples, 2 wells had 6-7 pH, 7 wells were more than 8 pH. The highest number of wells (38) found under 7-8 pH. Appearance is primary focus point to accept or reject on the basis of colour and odour. Dirty appearance were recorded higher in Bastar block (12), Tokapal (15) and Bastanar (29) comparatively green appearance which were present with Jagdalpur (8) and Bastar (8), whereas Lohandiguda had zero number of well in green appearance due to the area has undulating plain promote quick movement of rainwater to river drain. Muddy appearance is common in all blocks of the district. The suitability of dug wells lies among juncture of Bakawand, Jagdalpur, Bastar, Tokapal and eastern part of Lahandiguda for artificial ground water recharge might be possibility of increasing dug wells to recharge ground water. The correlation and covariance among the factors remained negative with each others.